Infrared Thermography for Thermo-Fluid-Dynamics - Astarita, Tommaso; Carlomagno, Giovanni Maria; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Infrared thermography is a measurement technique that enables to obtain non intrusive measurements of surface temperatures. One of the interesting features of this technique is its ability to measure a full two dimensional map of an object surface temperature and, for this reason, it has been widely used as a surface flow visualization technique. Since the temperature measurements can be extremely accurate, it is possible, by using a heat flux sensor, also to measure convective heat transfer coefficient distributions on a surface, making the technique de facto quantitative. This book, starting from the basic theory of radiation and heat flux sensors, guides, both the experienced researcher and the young student, in the correct application of this powerful technique to study convective heat transfer problems. A significant number of examples and applications are also examined in detail, often pointing out some relevant aspects.
Keywords: Engineering; Hydraulic engineering; Engineering; Engineering Fluid Dynamics; Measurement Science and Instrumentation; Security Science and Technology